Estimating the Frequency of Lyme Disease Diagnoses, United States, 2010–2018 - Kugeler, Kiersten J.; Schwartz, Amy M.; Delorey, Mark J.; Mead, Paul S.; Hinckley, Alison F. (Emerging infectious diseases, 2021)
By using commercial insurance claims data, we estimated that Lyme disease was diagnosed and treated in ≈476,000 patients in the United States annually during 2010-2018. Our results underscore the need for accurate diagnosis and improved prevention.